Tympanomastoid cholesterol Granulomas presenting as a Blue Eardrum in children - Zhengcai Lou (BMC Surgery, 2023)
Abstract Objective(s) This clinical study was performed to analyze the characteristics of cholesterol granuloma (CG) and evaluate our results in children. Methods The clinical records of children diagnosed with CG were retrospectively reviewed. Results The total of 17 children (20 ears) with CGs were included in this study. Endoscopy revealed pars flaccida retractions and lipoid tissue deposition behind the intact blue tympanic membrane (TM). CT scan revealed bony erosion and extensive soft tissue in the middle ear and mastoid. No ossicular chain destruction was found. All 20 ears underwent canal wall-up mastoidectomy and ventilation tube (VT) insertion, 3 sets of VT were performed in 5 ear and 2 sets in one. The residual perforation was seen in 2 ears following VT. The CT revealed well-pneumatized antra and tympanic cavities at postoperative 12–24 months. Conclusion(s) The CG should be suspected for the patients with yellow lipoid deposition behind the blue TM. CT of CG usually revealed bony erosion and extensive soft tissue in the middle ear and mastoid. Mastoidectomy combined with VT insertion and etiological treatment have a favorable prognosis for CG in children.